Socioeconomic differences in animal food consumption: Education rather than income makes a difference - Klink, Urte; Mata, Jutta; Frank, Roland; Schüz, Benjamin (Frontiers in Nutrition, 2022)
Background/Aims: Evidence points towards more sustainable and health-conscious dietary behaviours among individuals with higher socioeconomic status. However, these differences vary considerably depending on which indicator of socioeconomic status is examined. Here, we present a systematic parallel investigation of multiple indicators of socioeconomic status as predictors of animal food consumption frequency and selected food-related behaviours in Germany. Methods: Data from the German subsample of two large representative European consumer studies (Study 1 n=1954; Study 2 n=2045) was used. We assessed the associations between the socioeconomic indicators income, current occupation as well as education and consumption frequency of animal foods and selected food-related behaviours in separate ordinal logistic regressions. Results: Individuals with higher educational attainment engaged in more sustainable and health-conscious dietary behaviours, indicated by significant associations between educational attainment and the consumption frequency of animal foods. Low- and middle-income participants consumed processed meat more frequently (Study 1 only) and fish less frequently (Study 2 only) than participants with high income. Current occupation did not predict the consumption of animal foods or food-related behaviours. Most participants’ intake frequency of animal foods did not align with current dietary recommendations. Conclusion: Educational attainment appears to be the strongest and most consistent socioeconomic indicator of sustainable dietary choices in Germany based on current large, representative studies. Future efforts should be directed towards education interventions about nutrition and interpretation of food labels to compensate for differences in dietary behaviour among groups with different levels of education.